Flavonoids and Devosia sp SL43 cell-free supernatant increase early plant growth under salt stress and optimal growth conditions - Shah, Ateeq; Subramanian, Sowmyalakshmi; Smith, Donald L. (Frontiers in Plant Science, 2022)
Salt stress is a major threat to modern agriculture, significantly affecting plant growth and yield, and causing substantial economic losses. At this crucial time of increasing climate change conditions, soil salinity will continue to develop and become an even more serious challenge to crop agriculture. Hence, there is a pressing need for sustainable techniques in agricultural production that could meet the dual challenges of crop productivity and environmental instability. The use of biostimulants in agricultural production has greatly influenced plant health and global food production. In particular, the application of bioactive materials produced by beneficial microbes is becoming a common practice in agriculture and provides numerous benefits to plant growth and resistance to stressful conditions. In this research two biostimulants; a type of plant secondary metabolite (flavonoids) and a microbe-based material (CFS: Cell-Free Supernatant) containing active compounds secreted by a novel bacterial strain isolated from Amphecarpaea bracteata root nodules (Devosia sp - SL43), has been utilized to improve the growth and stress resistance of two major oil seed crops; canola and soybean, under optimal and salt stress conditions. Our findings suggested significant improvements in crop growth of canola and soybean following the application of both biostimulants. Under optimal growth conditions, soybean growth was significantly affected by foliar spray of flavonoids with increases in shoot fresh and dry weight, and leaf area, by 91, 99.5, and 73%, respectively. However, soybean growth was unaffected by flavonoids under salt stress. In contrast, CFS with a meaningful capacity to mitigate the negative effects of salinity stress improved soybean shoot fresh biomass, dry biomass, and leaf area by 128, 163 and 194%, respectively, under salt stress conditions. Canola was less responsive to both biostimulants, except for canola root variables which were substantially improved by flavonoid spray. Since this was the first assessment of these materials as foliar sprays, we strongly encourage further experimentation to confirm the findings reported here and to determine the full range of applicability of each of these potential technologies.